Malvaceae endémicas del Perú - Chanco, Magda (2006)
The Malvaceae are represented in Peru by 38 genera and 264 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly shrubs and herbs. Here we recognize 87 endemic species in 16 genera. Nototriche is the genus with the largest number of endemic species. Endemic Malvaceae species are found in many ecological regions, including High-Andean, Mesoandean, and Humid and Dry Puna, between 2500 m and 5100 m elevation. We applied IUCN categories and criteria to 84 species. Eleven endemic species have been recorded from Peru´s protected areas system.